Use of palm oil shells as aggregates in lightweight concrete - Abang Ali, Abang Abdullah (1986)
Malaysia is currently the world's largest producer of palm oil;producing 57 per cent of the current world output from some 1.3 million hectares of oil palm plantations. Palm oil shells generated as wastes from palm oil mills are hard and resistant to biodeterioration. It has a bulk density of about 600kg/m3. Thirty different concrete mixes using palm oil shells as coarse aggregates were tested in the laboratory to study the properties of the resulting concrete. In addition,flexural tests on reinforced concrete beams using a selected mix were conducted. Basic properties of the lightweight concrete using palm oil shells as aggregates were found to be satisfactory.